Letrozole in a low-cost in vitro fertilization protocol in intracytoplasmic sperm injection cycles for male factor infertility: A randomized controlled trial - Shiuli Mukherjee; Sunita Sharma; Baidya Nath Chakravarty (Wolters Kluwer Medknow Publications, 2012)
Introduction: Letrozole, a selective aromatase inhibitor, reduces the total dose of gonadotrophin required for inducing follicular maturation. We evaluated if incorporation of letrozole could be an effective alternative for low-cost in vitro fertilization (IVF) protocol particularly in intracytoplasmic sperm injection (ICSI) cycles where male factor infertility is the sole indication for IVF. Materials and Methods: It is a randomized controlled single-blind trial. 94 women with history of severe male factor infertility were selected. 42 women (study group) received letrozole, 5 mg daily from day 3-7 and recombinant FSH (rFSH) 75IU/day from day 5 continuously till hCG injection. 52 women (control group) underwent continuous stimulation by rFSH (150-225IU/day) from day 2. GnRH-antagonist (Inj. Orgalutran 0.25 ml sub-cutaneous) was started at maximum follicle size of 14 in both groups. Ovulation was triggered by 10,000IU of hCG followed by IVF-ET. Main outcome measures were total dose of rFSH (IU/cycle), terminal E2 (pg/ml), number of mature follicles, number of oocyte retrieved, transferable embryo, endometrial thickness, pregnancy rate and mean expenditure. Statistical analysis is done by using SPSS11. Results :0 As compared to control group (1756 ± 75IU), the study group i.e., Let-rFSH received (625 ± 98IU) significantly lower (P = 0.0001) total dose of rFSH. Terminal E2 was significantly lower (P = 0.0001) in study group than control (830 ± 36 vs. 1076 ± 41 pg/ml) with significant increment in endometrial thickness (P = 0.0008) in study group, (9.1 ± 0.32 vs. 8.7 ± 0.69) which maintained an improved pregnancy rate though nonsignificant. The risk of hyperstimulation had significantly (P = 0.01) reduced in study group than control (0 vs. 7).Treatment outcome in all other aspects including pregnancy rate were statistically comparable. Per cycle mean expenditure was reduced by 34% in study group than control. Conclusion: Adjunctive use of letrozole may be an effective mean of low-cost IVF therapy.